Monitoring of bacteriological quality of ballast water in Singapore by flow cytometry - Tay, Joo Hwa (2008)
Ballast water used in shipping operations may serve as a medium for the transfer of pathogenic microorganisms across different environments. This invasion may give rise to potentially significant economic, ecological and human health impacts. However, the adoption of an international standard for the microbiological quality of ballast water is complicated by the absence of fast and suitable methods for on-board bacteriological monitoring of ballast water. This study describes the development of simple and rapid flow cytometric methods for monitoring ballast water.